Atopy, non-allergic bronchial reactivity, and past history as determinants of work related symptoms in seasonal grain handlers. Issue 6 (June 1986) - Cookson, W O; Ryan, G; MacDonald, S; Musk, A W
Abstract : One hundred and five young subjects with little or no previous exposure to grain dust were studied before and after a seven week period of grain handling work to determine if there was an association between symptoms experienced at work and pre-employment respiratory symptoms, allergy skin test responses, and non-allergic bronchial reactivity. The incidence of work related symptoms was cough 18%, wheeze 13%, and dyspnoea 14%. The results showed that pre-employment history of respiratory symptoms, positive allergy skin test responses, and a high level of non-allergic bronchial reactivity were significantly associated with these symptoms. These measurements may be useful to predict symptoms associated with exposure to grain dust in new employees and the results suggest that these work related symptoms may be due to allergen induced asthma.